(untitled) (Revista Puertorriqueña de Psicologia, 2017)
High blood pressure is a serious heart disease that poses a potential health risk among minority men. Minority populations of Hispanic ethnic background often practice poor preventive behaviors and access to healthcare. In comparison to women, men show difficulties in perceiving threatening signs in their bodies, avoid routine checkups, and have poor adherence to treatment. According to the literature, men’s views about health are influenced by their perception of masculinity. The present study examined the experience of 14 Puerto Rican men with hypertension who participated in focus groups. Participants answered questions regarding health, social support, and masculinity. A thematic based coding strategy approach and discourse analyses were used. Protective factors, risk factors, and cultural values for prevention are discussed. The most frequent subthemes that emerged were emotional support based on interpersonal support and spiritual support. The study also found a relationship among the following themes: masculinity and health beliefs; emotional support and health beliefs, and masculinity. These findings provided an opportunity to address risk prevention including adherence to treatment from spouse and partner support as a cultural bridge between men and health in Puerto Rico. Finally, the findings could help to promote research on health psychology in minority populations and the challenges men face with seeking help.